NASIONALISME DALAM FILM âANALISIS SEMIOTIKA TENTANG REPRESENTASI NASIONALISME DALAM FILM DARAH GARUDAâ - , HANS HERMANG MINTANA, S.Sos, Dr. Phil. Ana Nadhya Abrar, M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study is titled "Nationalism in Film (Semiotics Analysis of Reprecentation Nationalism in the film Darah Garuda)". This thesis is based on the interest the authors look at the phenomenon of the film in conveying the message of nationalism in Indonesia. The author chose the film because the film Darah Garuda is a movie with the background of Indonesian struggle in maintaining its independence. This study aims to determine the representation of Nationalism in the Darah Garuda's movie. This type of research is a qualitative descriptive research. By using the theory of Roland Barthes Semiotics according comprehension and understanding of the theory of representation according to Stuart Hall. Through both theories Nationalism authors then seek representation in the film Darah Garuda. Representation of nationalism in the film "Darah Garuda" suggests most classical nationalism. That nationalism is always shown with lift arms. Attitude of nationalism in this film is shallow because nationalism judge only from the perspective of the military. But there are other important things in the realization of nationalism in our daily lives. This nation requires more human beings who can appreciate the integrity of all the components that make up this nation. Fighting for pride of this nation to the exclusion of the interests of certain groups. Nationalism is not just a symbol. Nationalism is demonstrated through real with our attitude. So nationalism is not only seen from the way we defend the State when in a state of war or always waving the flag, but nationalism is the attitude towards this nation. Love the attitude of this nation with our positive actions, forms a love of this nation can be done by acting honestly, discipline, did not dare to fight corruption and injustice, and tyranny. One of them gives the best performance for this nation.